Designing bioenergy landscapes to protect water quality. (September 2019) - Kreig, Jasmine A.F.; Ssegane, Herbert; Chaubey, Indrajeet; Negri, Maria C.; Jager, Henriette I.
Abstract: Practicing agriculture decreases downstream water quality when compared to non-agricultural lands. Agricultural watersheds that also grow perennial biofuel feedstocks can be designed to improve water quality compared to agricultural watersheds without perennials. The question then becomes which conservation practices should be employed and where in the landscape should they be situated to achieve water quality objectives when growing biofuel feedstocks. In this review, we focused on four types of spatial decisions in a bioenergy landscape: decisions about placement of vegetated strips, artificial drainage, wetlands, and residue removal. The appropriate tools for addressing spatial design questions are optimizations that seek to minimize losses of sediment and nutrients, reduce water temperature, and maximize farmer income. To accomplish these objectives through placing conservation practices, both field-scale and watershed-scale cost and benefits should be considered, as many biophysical processes are scale dependent. We developed decision trees that consider water quality objectives and landscape characteristics when determining the optimal locations of management practices. These decision trees summarize various rules for placing practices and can be used by farmers and others growing biofuels. Additionally, we examined interactions between conservation practices applied to bioenergy landscapes to highlight synergistic effects and to comprehensively address the question of conservation practice usage and placement. We found that combining conservation practices and accounting for their interactive effects can significantly improve water quality outcomes. Based on our review, we determine that by making spatial decisions on conservation practices, bioenergy landscapes can be designed to improve water quality and enhance other ecosystem services. Highlights: Management practices can be used on bioenergy landscapes to protect water quality. Field- and watershed-scale cost/benefits must be considered when placing practices. Decision trees can aid in determining optimal placement of management practices. Management practices interact in synergistic ways on bioenergy landscapes.